2001
DOI: 10.1007/pl00002390
|View full text |Cite
|
Sign up to set email alerts
|

Chronische Strahlenfolgen an den Zahnhartgeweben (“Strahlenkaries”) Klassifikation und Behandlungsansätze

Abstract: The documentation of early radiation effects on dental hard tissues seems to be neglectable. On the other hand the documentation of Late radiation effects has a high clinical impact. The identification of an initial lesion at the high-risk areas of the neck and incisal part of the tooth can lead to a successful therapy as a major prerequisite for orofacial rehabilitation. An internationally standardized documentation is a basis for the evaluation of the side effects of radiooncotic therapy as well as the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 15 publications
1
2
0
3
Order By: Relevance
“…One included study reported a decrease in the enamel microhardness in a region of the DEJ following in vivo and in vitro irradiation (18). In addition, another study found a significant increase in elastic modulus after simulated oral cancer radiotherapy at the evaluated sites in enamel and dentin, near the DEJ region (17); this was in agreement with two in vitro studies (26,27) that were not included, but in discordance with two other authors that did not observe any dental microhardness changes after in vitro irradiation (12,28). This divergence in the literature might be explained by the fact that the aforementioned studies did not evaluate the specific region of the DEJ.…”
Section: Discussionsupporting
confidence: 67%
“…One included study reported a decrease in the enamel microhardness in a region of the DEJ following in vivo and in vitro irradiation (18). In addition, another study found a significant increase in elastic modulus after simulated oral cancer radiotherapy at the evaluated sites in enamel and dentin, near the DEJ region (17); this was in agreement with two in vitro studies (26,27) that were not included, but in discordance with two other authors that did not observe any dental microhardness changes after in vitro irradiation (12,28). This divergence in the literature might be explained by the fact that the aforementioned studies did not evaluate the specific region of the DEJ.…”
Section: Discussionsupporting
confidence: 67%
“…While there is lack of data published on this topic, evidences suggest a conservative approach using adhesive restorations [ 8 ]. Haveman and Redding have shown that conventional glass-ionomer cement (GIC) had poorer results than the resin-modified glass-ionomer cements (RMGICs) and composite fillings in patients treated by radiotherapy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radio-xerostomia and radiation caries represent the major chronic side effects of head and neck irradiation [18]. Both the high consumption of short chain carbohydrates and reduced oral hygiene are known as promoting factors for radiation caries [19].…”
Section: Discussionmentioning
confidence: 99%